Cape Verde : Joint Staff Assessment of the Poverty Reduction Strategy Paper Preparation Status Report. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents the Joint Staff Assessment of Cape Verde's Poverty Reduction Strategy Paper Preparation Status Report (PRSP PSR). The Council of Ministers reviewed a first draft of the PRSP in April 2004. The authorities later prepared a second PRSP PSR for presentation to the Boards of the IMF and IDA. The report details main activities that have been completed to date, identifies remaining actions for completion, and notes that progress has been made in most of the areas previously identified by IMF staff as needing additional work.